(untitled) (Western European Journal of Medicine and Medical Science, 2026)
This article explores the cognitive outcomes observed following surgical treatment of hypertrophic tonsils and adenoids, primarily focusing on adenotomy and tonsillectomy. It gives a comprehensive analysis of the neurological, behavioral, and cognitive changes that might occur as a result of restoring airway functionality and improving sleep quality. The article addresses preoperative and postoperative cognitive states, pathophysiological mechanisms of cognitive impairment due to obstructive sleep disorders, and the impact of surgical interventions on academic performance, attention, memory, and executive functions in pediatric and adolescent populations.